A critical care pandemic staffing framework in Australia. Issue 2 (March 2021) - Marshall, Andrea P.; Austin, Danielle E.; Chamberlain, Di; Chapple, Lee-anne S.; Cree, Michele; Fetterplace, Kate; Foster, Michelle; Freeman–Sanderson, Amy; Fyfe, Rachel; Grealy, Bernadette A.; Hodak, Alison; Holley, Anthony; et al.
Abstract: Background: Pandemics and the large-scale outbreak of infectious disease can significantly impact morbidity and mortality worldwide. The impact on intensive care resources can be significant and often require modification of service delivery, a key element which includes rapid expansion of the critical care workforce. Pandemics are also unpredictable, which necessitates rapid decision-making and action which, in the lack of experience and guidance, may be extremely challenging. Recognising the potential strain on intensive care units (ICUs), particularly on staffing, a working group was formed for the purpose of developing recommendations to support decision-making during rapid service expansion. Methods: The Critical Care Pandemic Staffing Working Party (n = 21), representing nursing, allied health, and medical disciplines, has used a modified consensus approach to provide recommendations to inform multidisciplinary workforce capacity expansion planning in critical care. Results: A total of 60 recommendations have been proposed which reflect general recommendations as well as those specific to maintaining the critical care workforce, expanding the critical care workforce, rostering and allocation of the critical care workforce, nurse-specific recommendations for staffing the ICU, education support and training during ICU surge situations, workforce support, models of care, and de-escalation. Conclusion: These recommendations are provided with the intent that they be used to guide interdisciplinary decision-making, and we suggest that careful consideration is given to the local context to determine which recommendations are most appropriate to implement and how they are prioritised. Ongoing evaluation of recommendation implementation and impact will be necessary, particularly in rapidly changing clinical contexts.